2018
DOI: 10.5713/ajas.17.0471
|View full text |Cite
|
Sign up to set email alerts
|

Effect of mechanically deboned poultry meat content on technological properties and sensory characteristics of lamb and mutton sausages

Abstract: ObjectiveThis study aimed to develop a value-added product concerning technological and sensory characteristics changes of the use of mechanically deboned poultry meat (MDPM) as meat replacer in lamb and mutton emulsion-type sausages (mortadella).MethodsSausages were produced with lamb and mutton and with different contents of MDPM. Six treatments, using lamb or mutton and 0%, 30%, and 60% of MDPM in relation to the meat batter, were produced and analyzed for pH, proximal composition, calcium and residual nitr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
1
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 27 publications
1
9
1
1
Order By: Relevance
“…F-MSC2 was harder (P < 0.05) than both F-MSC1 and F-CBT, which were not different from each other (P > 0.05). These results are in contrast with previous literature, which shows a decrease in compressive strength with the addition of MSC (Daros et al, 2005;Massingue et al, 2018). In a companion study to this one (Miller et al, 2020), it was observed that the rheological behavior of myofibrillar extracts of these two MSC was similar, despite differences in proximate composition and collagen content.…”
Section: Texture Profile Analysiscontrasting
confidence: 95%
“…F-MSC2 was harder (P < 0.05) than both F-MSC1 and F-CBT, which were not different from each other (P > 0.05). These results are in contrast with previous literature, which shows a decrease in compressive strength with the addition of MSC (Daros et al, 2005;Massingue et al, 2018). In a companion study to this one (Miller et al, 2020), it was observed that the rheological behavior of myofibrillar extracts of these two MSC was similar, despite differences in proximate composition and collagen content.…”
Section: Texture Profile Analysiscontrasting
confidence: 95%
“…Sensory analysis was fulfilled behind the National Research Ethics System (SISNEP, Brazil) permission under protocol CAAE 35793414.5.0000.5588. To describe the sensory characterization of each product formulated, the check-all-that-apply (CATA) questions were used as proposed by JORGE et al, 2015and MASSINGUE et al, (2018). Twenty untrained participants were firstly met to define the CATA terms.…”
Section: Methodsmentioning
confidence: 99%
“…Ayrıca EAE parçalarının daha homojen ve ince kıyılmış et matriksinin içerisine gömülü durumda olduğu hindi sosisi gibi ürünlerde, yapıştırıcı bir matriks olarak boşlukların doldurulmasında MAE kullanılmaktadır (1,4,39). Brezilya'da kuzu ve koyun sosisi olarak bilinen Mortadella üretiminde, ürünün daha ekonomik ve tüketicinin damak zevkine daha fazla hitap edebilmesi amacı ile farklı oranlarda MAKE kullanıldığı bir çalışmada, çıkma koyun eti yerine % 30 oranında MAKE ilavesinin tüketici tarafından daha fazla tercih edilen pembe parlak görünüm ile yumuşak ve yağlı dokuyu sağlayabildiği belirlenmiştir (33). Song ve ark.…”
Section: Kullanım Alanlarıunclassified